THE ROLE OF TEACHERS IN INTEGRATING DIGITAL TAJWID APPLICATIONS IN AL-QUR'AN READING LEARNING IN ISLAMIC BOARDING SCHOOLS - Saputra, Rizki; Kartubi, Kartubi; Saputra, Edi (Sekolah Tinggi Agama Islam Al Hidayah, 2026)
The ability to read the Qur’an correctly in accordance with tajwid rules is a fundamental competence in Islamic education and has traditionally been taught in Islamic boarding schools through methods such as talaqqi and musyāfahah. However, contemporary Qur’anic learning faces challenges related to technological developments, changing student characteristics, and the practical limitations of classical learning methods. This study aims to examine teachers’ strategies in integrating a digital tajwid learning application, Learn Quran Tajwid, as a supporting medium in Qur’an reading instruction within a pesantren context. This research employed a qualitative field study with a descriptive approach conducted at Darul Haq Muaro Jambi Islamic Boarding School from October 2025 to January 2026. Data were collected through observations, interviews, and documentation involving tahsin/tahfiz teachers and MTs-level students, particularly Grade VII students. The data were analyzed through the stages of data reduction, categorization, data presentation, and conclusion drawing. The findings show that the application contributes positively to improving students’ Qur’an reading proficiency, particularly in reading fluency, accuracy of makhārijul ḥurūf, and understanding of tajwid rules. Nevertheless, the effectiveness of the application depends largely on teachers’ roles in guiding, managing, and integrating digital media with traditional learning methods. Several challenges were identified, including limited facilities, uneven digital literacy among teachers, and student discipline in using technology. The study concludes that digital tajwid applications such as Learn Quran Tajwid can function effectively as complementary learning tools when supported by teacher-centered strategies, systematic planning, and institutional support without undermining the traditional values of pesantren education.